Non-invasive 40-Hz Light Flicker Ameliorates Alzheimer’s-Associated Rhythm Disorder via Regulating Central Circadian Clock in Mice - Yao, Youli; Ying, Ying; Deng, Qiyu; Zhang, Wenjiang; Zhu, Huazhang; Lin, Zhenglong; Zhang, Shengli; Ma, Junxian; Zhao, Yingying (Frontiers in Physiology, 2020)
Alzheimer’s disease (AD) patients often exhibit perturbed circadian rhythm with fragmented sleep before disease onset. This study was designed to evaluate the effect of 40-Hz light flicker on circadian rhythm in an AD mouse model (APP/PS1). Locomotor rhythms recordings was conducted to examine the circadian clock rhythm in APP/PS1 mice. Molecular biology analyses, including western blot and real-time qPCR assays, were conducted to assess the changes in circadian locomotor output cycles kaput (CLOCK), brain and muscle arnt-like protein-1 (BMAL1), and period 2 (PER2). In addition, to determining the direct effect of 40-Hz light flicker on hypothalamic central clock, whole-cell voltage-clamp electrophysiology was employed to record individual neurons of suprachiasmatic nucleus (SCN) sections. The results reported herein demonstrate that 40-Hz light flicker relieves circadian rhythm disorders in APP/PS1 mice and returns the expression levels of key players in the central circadian clock, including Clock, Bmal1 and Per2, to baseline. Moreover, the frequency of spontaneous inhibitory postsynaptic currents (sIPSCs) in SCN neurons is significantly lower in APP/PS1 mice than in the control, and the amplitude of sIPSCs is decreased. Exposure to 40-Hz light flicker significantly increases the sIPSCs frequency in SCN neurons of APP/PS1 mice, with little effect on the amplitude. However, the frequency and amplitude of spontaneous excitatory postsynaptic currents (sEPSCs) are both unaffected by 40-Hz light flicker. The data suggests that 40-Hz light flicker can ameliorate AD-associated circadian rhythm disorders, presenting a new type of therapeutic treatment for rhythm disorders caused by AD.